Seni Dakwah Kyai Kuswaidi Syafi’ie Melalui Komunikasi Interpersonal pada Program Salawat Muhibbin di Karangcempaka Bluto Sumenep - Moh Zuhdi (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
This study aims to explore the art of da‘wah practiced by Kyai Kuswaidi Syafi’ie through interpersonal communication in the Salawat Muhibbin Program in Karangcempaka Village, Bluto District, Sumenep Regency. The research employs a qualitative analytical method, with data collected through in-depth interviews, participant observation, and document analysis. The theoretical framework draws upon Interpersonal Communication Theory, Symbolic Interactionism, and Empathy Theory in communication. The findings reveal that Kyai Kuswaidi applies four forms of da‘wah artistry. First, empathetic communication that takes into account the psychological conditions of the congregation. Second, interactive and participatory communication that encourages active engagement among congregants. Third, the use of religious humor to create a relaxed atmosphere while conveying moral messages. Fourth, a profound personal approach aimed at fostering emotional closeness with the congregation. These approaches are shown to be effective in enhancing the acceptance of da‘wah messages, strengthening social bonds among congregants, and rendering religious preaching more responsive to the needs of rural communities. Through these communicative arts, Kyai Kuswaidi’s da‘wah serves as a role model for the delivery of religious messages grounded in strong interpersonal communication competence, thereby promoting a more humanistic model of da‘wah.